Tiberiu Olah’s Evenimente 1907 (Events 1907). Modernism Disguised in a Historical Movie Score - LUPU, Olguța (Studia Universitatis Babes-Bolyai Musica, 2024)
Tiberiu Olah’s Evenimente 1907 (Events 1907), originally the music for the film Răscoala (The Uprising) after Liviu Rebreanu’s novel, can be considered a work inspired by a page in Romanian national history involving a large mass of people, and as such in tune with the themes pushed by the Communist ideology. But this layer of meaning runs in parallel with another one, indicative of the modern, elitist music from outside Romania, more precisely of works by composers of the Second Viennese School. The two layers, to all appearances completely contradictory, prove to be parts of a single whole. By managing, like some Till Eulenspiegel (or his Romanian relative Păcală), to dissimulate the nod to modernism in the clothes of the music for a historical film, Olah offers a model both of pluristratification of meaning and of harmonization of opposites.